Psychoeducation for schizophrenia in the Czech Republic: curriculum modification based on opinions of service users and providers - Bankovská Motlová, Lucie; Dragomirecká, Eva; Blabolová, Anna; Španiel, Filip; Slováková, Andrea (Academic psychiatry, 2015)
OBJECTIVE: The authors examined current knowledge about psychoeducation for schizophrenia in Czech Republic. METHODS: The authors sent a screening survey to 550 mental health-care facilities and administered a detailed questionnaire to 113 providers of mental health and social services and to 200 service users. The authors also carried out 14 focus groups and 16 individual interviews. RESULTS: Forty-six departments provided some type of psychoeducation for schizophrenia; of these, 16 provided family psychoeducation for patients and relatives and 1 provided psychoeducation only for relatives. Service users who received psychoeducation performed significantly better in the test of knowledge than did service users who did not receive psychoeducation. CONCLUSION: The authors propose a service user-driven curriculum based on information delivery followed by skills training. Psychiatrists should learn to explain schizophrenia relapse neurobiology to laypeople and to address relatives' frustrations.
Keywords: Patient Education as Topic; sociální práce psychiatrická; klinické kompetence; průzkumy a dotazníky; osoby pečující o pacienty; Needs Assessment; postoj zdravotnického personálu; služby péče o duševní zdraví; Surveys and Questionnaires; odhad potřeb; Mental Health Services; lidé; vzdělávání pacientů jako téma; Clinical Competence; sběr dat; Caregivers; Focus Groups; schizofrenie; Attitude of Health Personnel; prognóza; Humans; emoční inteligence; Czech Republic; Data Collection; Health Knowledge, Attitudes, Practice; Schizophrenia; zjišťování skupinových postojů; zdraví - znalosti, postoje, praxe; Prognosis; Česká republika; psychiatrie; Social Work, Psychiatric; Psychiatry; Emotional Intelligence